2013
DOI: 10.1176/appi.neuropsych.12010003
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Volumes in Patients With Chronic Combat-Related Posttraumatic Stress Disorder: A Systematic Review

Abstract: The authors and others have recently demonstrated that veterans with chronic combat-related PTSD (CR-PTSD) have a twofold increased risk of dementia. To understand this increased incidence, they performed a systematic review of the literature on neuroanatomical differences between veterans with chronic CR-PTSD and control subjects (22 included studies). The hippocampus was most commonly and consistently reported to differ between groups, thereby suggesting the hypothesis that PTSD is associated with smaller hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…38 A recent systematic review found that smaller total hippocampal volume is the most frequently reported structural difference in studies comparing individuals with PTSD to healthy control subjects. 39 This review and an older meta-analysis both reported mostly right-sided reductions. 39,40 Similarly, a recent study in combat veterans with chronic and current PTSD found that PTSD duration was inversely correlated with hippocampal volume, but only on the right.…”
Section: Functional Neuroimagingmentioning
confidence: 94%
See 3 more Smart Citations
“…38 A recent systematic review found that smaller total hippocampal volume is the most frequently reported structural difference in studies comparing individuals with PTSD to healthy control subjects. 39 This review and an older meta-analysis both reported mostly right-sided reductions. 39,40 Similarly, a recent study in combat veterans with chronic and current PTSD found that PTSD duration was inversely correlated with hippocampal volume, but only on the right.…”
Section: Functional Neuroimagingmentioning
confidence: 94%
“…39 This review and an older meta-analysis both reported mostly right-sided reductions. 39,40 Similarly, a recent study in combat veterans with chronic and current PTSD found that PTSD duration was inversely correlated with hippocampal volume, but only on the right. 41 However, two metaanalyses that focused on whole brain studies that included trauma-exposed control subjects reported left laterality.…”
Section: Functional Neuroimagingmentioning
confidence: 94%
See 2 more Smart Citations
“…The time course of structural change is much longer than the half-life of cortisol; cortisol elevation needs to be sustained to cause longer-lasting brain changes. Smaller hippocampi are common among people with PTSD or trauma exposure [62, 63] and they also are linked to increased risk for PTSD development [64] so the causative relationship is uncertain. Further, PTSD sufferers are at higher risk of dementia [65] and those with smaller hippocampi have increased the risk of dementia [66].…”
Section: Measurement Of Stressmentioning
confidence: 99%